Manajemen Keuangan Keluarga dan Pengaruhnya terhadap Keharmonisan Rumah Tangga pada Pasangan Suami Istri - Nurjanis (Jurnal Indragiri Penelitian Multidisiplin, 2025)
This study aims to examine the influence of family financial management on marital harmony among married couples. A household is not only built on the foundation of love and affection but also relies on the couple’s ability to manage economic resources wisely. Financial issues often become the main trigger of conflict in a marriage, whether due to a lack of planning, imbalance between income and expenditure, or a lack of transparency in financial decision-making. This research uses a qualitative approach with a case study method involving five married couples residing in Pekanbaru City, with a minimum marriage duration of five years. Data collection techniques include in-depth interviews, observation, and documentation. Data analysis was carried out through data reduction, data display, and conclusion drawing, with validation conducted through source triangulation. The results of the study show that couples who engage in joint financial planning, share responsibilities fairly, and build open communication regarding financial matters tend to have more harmonious, stable, and low-conflict households. Conversely, couples without a clear financial system are more vulnerable to tension, especially when facing economic pressure. Thus, family financial management plays a crucial role in creating a healthy and sustainable marital relationship.